An exploration into consumers' e-learning strategies. Issue 2 (14th March 2019) - Steils, Nadia; Decrop, Alain; Crié, Dominique
Abstract : Purpose: As traditional paper manuals and step-by-step instructions have shown to discourage new product learning because of a lack of exploration, the purpose of this paper is to investigate consumer learning from an online and andragogical, that is, adult learning, perspective by identifying relevant consumer e-learning processes in new product learning. Design/methodology/approach: This paper uses thematic and trace analyses on a multi-method data collection, that is, extant e-learning courses, in-depth interviews and non-participant observations. Findings: Emerging findings give light on customized, interactive and iterative e-learning processes depending on consumers' previous experiences, their learning orientation as adult learners and the characteristics of the online environment. Results provide evidence for the existence of three learning strategies and show how the online environment comes shifting traditional consumer learning paradigms. Originality/value: This paper contributes to the literature on consumer behavior on two levels. First, the findings highlight the importance of taking an andragogical standpoint to provide a more nuanced and realistic view on consumers' learning processes in new product learning. Second, the results show how the exploration and interactivity provided by the online environment present beneficial prerequisites for effective consumer learning. More than just being an alternative, online learning is complementary to offline modes of learning to improve consumers' overall learning experience.